2016
DOI: 10.1517/14712598.2016.1145651
|View full text |Cite
|
Sign up to set email alerts
|

Current clinical evidence for the use of mesenchymal stem cells in articular cartilage repair

Abstract: The article demonstrates robust clinical evidence that MSCs have significant potential for the regeneration of hyaline articular cartilage in patients. The majority of clinical trials to date have yielded significantly positive results with minimal adverse effects. However the clinical research is still in its infancy. The optimum MSC source, cell concentrations, implantation technique, scaffold, growth factors and rehabilitation protocol for clinical use are yet to be identified. A larger number of randomised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 80 publications
0
34
0
Order By: Relevance
“…Administration of bone marrow-derived mesenchymal stromal cells (MSCs) in sites of cartilage injury is a valuable option to enhance the local processes of cartilage repair [7][8][9][10] due to the chondroreparative activities of these cells, [11][12][13] especially when provided as marrow concentrates in their natural, clinically relevant microenvironment using off-the-shelf, minimally invasive procedures. 14,15 Still, even with such convenient techniques, the long-term quality of repair tissue in the treated lesions remains unsatisfactory, with production of a poor fibrocartilaginous repair tissue (type-I collagen) unable to bear prolonged mechanical stress.…”
Section: Introductionmentioning
confidence: 99%
“…Administration of bone marrow-derived mesenchymal stromal cells (MSCs) in sites of cartilage injury is a valuable option to enhance the local processes of cartilage repair [7][8][9][10] due to the chondroreparative activities of these cells, [11][12][13] especially when provided as marrow concentrates in their natural, clinically relevant microenvironment using off-the-shelf, minimally invasive procedures. 14,15 Still, even with such convenient techniques, the long-term quality of repair tissue in the treated lesions remains unsatisfactory, with production of a poor fibrocartilaginous repair tissue (type-I collagen) unable to bear prolonged mechanical stress.…”
Section: Introductionmentioning
confidence: 99%
“…Fibrocartilaginous tissue cannot meet the needs of the joint exercise, which leads to the scope of the lesion expanding causing arthritis and leading to intractable pain and dysfunction. Therefore, the repair of articular cartilage injury has always been a difficult and hot spot in the field of orthopedic research [36]. …”
Section: Introductionmentioning
confidence: 99%
“…Soler et al (35) developed a series of clinical trials in which autologous MSCs were injected into the body after in vitro expansion, resulting in regenerative cartilage in the injured area and therefore, concluded that the therapy is safe and viable. Existing studies have revealed that MSCs' cultured and expanded cartilage repair effect is equally effective as other therapies (36). Autologous chondrocytes and MSCs have their own advantages and disadvantages.…”
Section: In Vitro Culture Of Expanded Mscs For Repair Of Articular Camentioning
confidence: 99%